MULTICOLLECTOR ICP-MS ANALYSIS OF PB ISOTOPES USING A 207PB-204PB DOUBLE SPIKE DEMONSTRATES UP TO 400 PPM/AMU SYSTEMATIC ERRORS IN TL-NORMALIZATION - Thirlwall M.F. (My University, 2002)
Pb isotope analyses using multicollector magnetic sector inductively coupled plasma mass spectrometers (ICP-MS) may potentially be corrected for mass bias, a major source of uncertainty, by assuming that the mass bias for Tl is similar to that of Pb. Around 7 ng of Pb has been analysed in this study using a Micromass IsoProbe MC-ICP-MS. With detailed attention to backgrounds arising from instrument memory and tailing from adjacent peaks, external precision of 55-180 ppm 2sd has been achieved over a year on Pb isotope ratios normalized to constant 208Pb/206Pb. This involves use of a wide range of SRM981 solutions and two different nebulizers. Mean ratios are very close to multidynamic TIMS data normalized in the same way, provided that anomalous TIMS behaviour of 207Pb [Chem. Geol. Isot. Geosci. Sect. 163 (2000) 299] is corrected to the least fractionated ratios measured. Tl-normalized Pb isotope ratios vary substantially between different SRM981 solutions and between nebulizers, with external precision over the year being up to 541 ppm (2sd) on 208Pb/204Pb. However, a 207pb-204pb double spike (DS) can accurately correct for mass bias on the IsoProbe, and external precision of at worst 245 ppm (2sd) on 208Pb/204Pb has been obtained over the year using a wide range of SRM981 solutions and two different nebulizers. Mean ratios on DS-corrected SRM981 and silicate samples are within error of DS-TIMS results, even using an independent calibration for the DS on the IsoProbe. A new 208Pb/206Pb value for SRM981 of 2.1677+/-2 is proposed, normalized to SRM982 208Pb/206Pb=1.00016. Use of SRM981 to optimize the 205Tl/203Tl normalizing ratio would give Tl-normalized sample ratios ~400 ppm/amu higher than those calculated using the DS correction. It is shown that these problems with Tl normalization cannot result from isobaric interferences, but they appear to be due to unusual solution chemistry of Tl in the nebulizer.
Keywords: LEAD; MASS BIAS; ICP-MS; ISOTOPES; ERRORS; TIMS